Chaotic Particle Swarm Optimisation Algorithm Based Quadrotor Control - M. Buğrahan ARTUÇ; İsmail BAYEZİT (Havacılık ve Uzay Teknolojileri Dergisi, 2021)
Unmanned aerial vehicles are currently used for civil and military purposes. Today, quadrotor vehicles are highly important example of non-conventional underactuated rotary-wing platforms. In addition, quadrotors include complex nonlinearities compared to conventional aerial vehicles due to internal instability. Therefore, Chaotic Particle Swarm Optimisation Algorithm is employed to overcome and regulate this issue. In this study, a nonlinear system model of the IRIS+ quadrotor is used and the classical PID control is designed using CPSO algorithm. Chaotic Particle Swarm Algorithm is used to emerge a stable reference model for robust adaptive control of the experimental testbed.